ANALISIS STRATEGI UMKM (USAHA MIKRO KECIL MENENGAH)DALAM MENGHADAPI MEA (MASYARAKAT EKONOMI ASIA) (STUDI KASUS: KECAMATAN TEGALREJO KOTA YOGYAKARTA) - Ika Afianita Suherningtyas (Universitas Pendidikan Ganesha, 2018)
Asean Economic Community (AEC) is a realization of free market in Southeast Asia, consequence MEA are free flow of ASEAN countries in the form of goods, services, investment, labor, and capital. This condition requires Indonesian people, especially entrepreneurs of UMKM (Usaha Kecil Mikro Menengah) to be able to adjust business competition globally. Tegalrejo Sub-district is a sub-district with UMKM potential of 890 (Disperindakop, 2017), this condition is supported by strategic location on busy traffic line and around tourism area. This research uses qualitative method by collecting secondary data and doing interview with UMKM in Tegalrejo Sub-district. Through the results of data processing, it can be seen that the analysis of UMKM strategies in dealing with MEA among others related to the quality of human resources, business management, internet marketing, tourism potential development, and local products. Research on the strategy of UMKM Tegalrejo District makes UMKM can grow globally and reduce unemployment.Key words: AEC, UMKM, strategy